2019
DOI: 10.4103/ua.ua_43_18
|View full text |Cite
|
Sign up to set email alerts
|

Single-step dilatation in percutaneous nephrolithotomy, its safety and efficacy: A prospective, single-center study

Abstract: Background: Percutaneous nephrolithotomy (PCNL) is gold standard technique for the treatment of renal calculi larger than 2 cm or complex renal calculi. Establishment of nephrostomy tract is the important step during PCNL. Hence, this study was conducted to evaluate the effectiveness of single-step dilatation in patients with renal calculi undergoing PCNL. Methods: This is a prospective, single-center study conducted between August 2014 and December 2017. Patient who un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…In an analysis of the international prospective database of more than 5.800 cases, de la Rosette et al reported low-grade complications (grade 1 and grade 2) in 16.4% of cases, grade 3a and 3b complications in 3.6% of cases, and severe complications in 0.5% of the cases, while there were no complications in 79.5% of the cases. [18] Girisha et al [8] reported a 20% complication rate in 332 patients who underwent OD-alone, and there were no major complications. Injury to the kidney collecting system was reported in 5.2% of the cases, while urinoma formation was determined in only 0.2% of the cases.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In an analysis of the international prospective database of more than 5.800 cases, de la Rosette et al reported low-grade complications (grade 1 and grade 2) in 16.4% of cases, grade 3a and 3b complications in 3.6% of cases, and severe complications in 0.5% of the cases, while there were no complications in 79.5% of the cases. [18] Girisha et al [8] reported a 20% complication rate in 332 patients who underwent OD-alone, and there were no major complications. Injury to the kidney collecting system was reported in 5.2% of the cases, while urinoma formation was determined in only 0.2% of the cases.…”
Section: Discussionmentioning
confidence: 97%
“…In the literature, it has been reported that the one-shot kidney dilatation technique is a safe method that has lower radiation exposure with less cost. [7,8] The goal of one-shot dilatation is to provide percutaneous canal formation in a single step without the need for serial dilatations.…”
Section: Introductionmentioning
confidence: 99%
“…It can fix the kidney during the tract dilation maneuver and also help introduce instruments for tract dilation, such as the fasciacutting needle and nephrostomy balloon catheter. Moreover, it was reported that technique of one shot renal dilation using nephrostomy balloon were safer and more effective than metal telescopic dilation or serial Amplatz dilation for nephrostomy tract dilation, resulting in a shorter tract dilatation fluoroscopy time and less hemoglobin drop [ 28 29 30 ]. Therefore, the nephrostomy tract can be made faster, safer, and more easily than the conventional method.…”
Section: Discussionmentioning
confidence: 99%
“…After its first description in 1976 by Fernström and Johansson, percutaneous nephrolithotomy (PCNL) has now become the standard of care for the management of renal stone disease. [ 1 2 ] It is a minimally invasive technique associated with higher success rate and lower complications for the efficient management of renal calculi >2 cm in diameter, staghorn calculi, and larger lower calyceal calculi. [ 3 4 ]…”
Section: Introductionmentioning
confidence: 99%
“…Gaining access to the pelvi-calyceal system by renal puncture and subsequent dilatation of the tract is a crucial and challenging step in this procedure and is conventionally done by one of the following three techniques – serial Alken metal telescope dilators, semi-rigid Amplatz sequential fascial dilators, and single-step balloon dilator. [ 1 5 ] The reusable metal telescopic dilators are economical, and there is less blood loss because of the tamponade effect on renal parenchyma by metal dilators. Sequential fascial dilators are disposable, and there is possibility of more blood loss as the tamponade effect is lost during sequential exchange of these fascial dilators.…”
Section: Introductionmentioning
confidence: 99%